2015
DOI: 10.3109/10428194.2014.1003055
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib induces paradoxical phosphorylation of the extracellular signal-regulated kinase pathway in acute myeloid leukemia cells lacking FLT3-ITD mutation

Abstract: Gain-of-function mutations in the RAS and FLT3 genes are frequently found in cells of acute myeloid leukemia (AML), leading to constitutive activation of signaling pathways that regulate fundamental cellular processes, and are therefore attractive targets for AML therapy. The multi-targeted kinase inhibitor sorafenib is efficacious in AML with FLT3-internal tandem duplication (ITD), but resistance to therapy is an important clinical problem. It is unclear whether AML lacking FLT3-ITD responds to sorafenib. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Consistent with our data, earlier studies have also shown the inhibitory effect of sorafenib on ERK phosphorylation and proliferation of flt-3-mutant leukemia cells (14,15). Tyrosine kinase inhibitors, such as dasatinib and imatinib, have been shown to impede immune escape mechanisms in patients with CML by downregulation of MDSCs, simultaneously increasing T cell IFN-γ production (42).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with our data, earlier studies have also shown the inhibitory effect of sorafenib on ERK phosphorylation and proliferation of flt-3-mutant leukemia cells (14,15). Tyrosine kinase inhibitors, such as dasatinib and imatinib, have been shown to impede immune escape mechanisms in patients with CML by downregulation of MDSCs, simultaneously increasing T cell IFN-γ production (42).…”
Section: Discussionsupporting
confidence: 91%
“…Sorafenib is an inhibitor of several serine and threonine kinases, such as RAF, and tyrosine kinases, including VEGFRs. Sorafenib has been shown to block ERK activity and proliferation of flt-3-mutant acute myeloid leukemia cells (14,15) and reduce ERK phosphorylation of endothelial progenitor cells from patients with HCC (21). Activated ERK is a key downstream component of this signaling cascade that sorafenib is targeting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one should notice that 1 µM is a relatively low concentration for Sorafenib as the maximal plasma concentration of Sorafenib in patients reaches 10 to 21 µM [40–42]. Previous reports confirm that Sorafenib causes ERK paradoxical activation at low doses [4345]. However, at higher doses (5 µM and 10 µM), Sorafenib caused ERK inhibition (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…However, the clinical efficacy of sorafenib was limited due to low sensitivity and high drug resistance ( 5 ). The first- and second-line drugs for advanced HCC require further development ( 6 ). Improving the efficacy of sorafenib has been popular in the discussion of HCC chemotherapy.…”
Section: Introductionmentioning
confidence: 99%